PENGARUH UMUR PERUSAHAAN, LEVERAGE, TOTAL ARUS KAS DAN UKURAN PERUSAHAAN TERHADAP FINANCIAL DISTRESS PADA PERUSAHAAN TEKSTIL DAN GARMEN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2019-2021 - Mufidah, Sevinatu; Istanti, Sri Layla Wahyu (Jurnal Riset Akuntansi Politala, 2024)
This research was used to determine the effect of company age, leverage, total cash flow and company size on financial distress in textile and garment companies listed on the Indonesia Stock Exchange in 2019-2021. The sampling method for this research uses a purposive sampling method. The analysis technique used is multiple linear regression and the type of research data is quantitative. The research results show that leverage has a significant positive effect on financial distress in textile and garment companies listed on the Indonesia Stock Exchange in 2019-2021. On the other hand, company age, total cash flow, and company size have an insignificant negative effect on financial distress. It is hoped that the results of this research can be a basis for management to make improvements when the company shows financial problems. It is hoped that this research will help them choose which companies they will invest in.